Regional interests in Europe : Wales and Saxony as modern regions - Mathias, Jörg (Cass series in regional and federal studies., 2004)
The question of how to organize and manage sustainable regional development has recently come to the fore in many places across the industrialized countries of Central and Western Europe, and especially within the European Union (EU). This book looks at the home-grown natural, economic and social, socio-political, political and administrative conditions which policy makers face, while also being subjected to numerous external influences. Political actors in less important EU regions attempt to create and implement strategies of regional development in the context of regional policy-maki.